Early childhood deprivation and the impact of negative life events on mental health in later life: a test of the stress sensitization hypothesis - Jala Rizeq; Mark Kennedy; Kirellos Miseih; Wangjingyi Liao; Edmund J. S. Sonuga-Barke (Frontiers in Psychiatry)
IntroductionEarly life exposure to adversity and stress has been shown to sensitize young people to later negative life events (LEs), leading to increased susceptibility to mental health problems. We explored this question by testing whether exposure to severe institutional deprivation moderated the effect of adolescent exposure to LE on early adult depression and anxiety. To test the specificity of these effects, we contrasted the effects on these outcomes with neuro-developmental problems (autism and disinhibited social engagement), known from previous studies to be associated with deprivation from early childhood.MethodsParticipants were 170 adoptees from the English and Romanian Adoptees study. Of these, 124 (66 females) grew up as infants and small children in severely depriving Romanian orphanages before being adopted into UK families before the age of 43 months. The remainder were UK adoptees (16 females) with no history of deprivation who were placed before the age of 6 months. For this analysis, data on emotional problems, autism, and disinhibited social engagement were used at both age 15 years and in early adulthood (23–25 years) using standardized questionnaire and interview measures. Exposure to independent, dependent, and peer-related LE was measured at age 15 years.ResultsIn all models, there were continuities in all outcomes between adolescence and adulthood (ps < .05). Dependent LE had a main effect on emotional symptoms, with higher exposure to dependent LE predicting an increase in emotional symptoms between age 15 and young adulthood. For independent and dependent LE, there were no interactions between deprivation and LE. For peer-related LE, the interaction was significant for emotional problems, but not deprivation-specific problems (i.e., autism/disinhibited social engagement)—the group of individuals exposed to early extreme deprivation and elevated peer-related LE had elevated emotional problems.DiscussionThere was no evidence that early severe institutional deprivation increased susceptibility to depression and anxiety following exposure to independent or dependent LE in general. However, it appeared to sensitize adolescents to the effects of peer-related LE specifically. We discuss possible mechanisms by which difficulties in peer relations might influence the emergence of depression and anxiety to already vulnerable individuals.